Pengaruh Dukungan Keluarga Terhadap Perilaku Pengendalian Tekanan Darah Pada Penderita Hipertensi Lansia Di Puskesmas Sumbang 1 - Triono, Agus; Hikmawati, Isna (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: Hypertension is a condition in which the systolic blood pressure is 140 mmHg and the diastolic is 90 mmHg. The elderly are at high risk of degenerative diseases, one of which is hypertension. The family has an important role in the process of supervision, maintenance, and prevention of complications of hypertension at home. Objective: The aim of this study was to determine the effects of family support on blood pressure control behavior in elderly hypertensive patients at Puskesmas Sumbang I.Method: This research was conducted using Quantitative with a Quasy-Experimental design with a nonequivalent control group design. The sampling technique in this study used purposive sampling with 36 respondents.Results: The results of the analysis with the independent t test after intervention guidelines were given showed that there was an effect of family support on blood pressure control behavior in the experimental and control groups (p value < 0.05). In addition, the results of calculations with the formula effect size showed that the provision of family support intervention had a high effect on systole and a high effect on diastole.Conclusion: In conclusion, there is an influence of family support on blood pressure control behavior in elderly hypertension patients and has a high effect on systole and a high effect on diastole.Â